Enhanced creep performance in a polycrystalline superalloy driven by atomic-scale phase transformation along planar faults. (1st January 2021) - Lilensten, Lola; Antonov, Stoichko; Gault, Baptiste; Tin, Sammy; Kontis, Paraskevas
Abstract: Predicting the mechanical failure of parts in service requires understanding their deformation behavior, and associated dynamic microstructural evolution up to the near-atomic scale. Solutes are known to interact with defects generated by plastic deformation, thereby affecting their displacement throughout the microstructure and hence the material's mechanical response to solicitation. This effect is studied here in a polycrystalline Ni-based superalloy with two different Nb contents that lead to a significant change in their creep lifetime. Creep testing at 750°C and 600 MPa shows that the high-Nb alloy performs better in terms of creep strain rate. Considering the similar initial microstructures, the difference in mechanical behavior is attributed to a phase transformation that occurs along planar faults, controlled by the different types of stacking faults and alloy composition. Electron channeling contrast imaging reveals the presence of stacking faults in both alloys. Microtwinning is observed only in the low-Nb alloy, rationalizing in part the higher creep strain rate. In the high-Nb alloy, atom probe tomography evidences two different types of stacking faults based on their partitioning behavior. Superlattice intrinsic stacking faults were found enriched in Nb, Co, Cr and Mo while only Nb and Co was segregated at superlattice extrinsic stacking faults. Based on their composition, a local phase transformation occurring along the faults is suggested, resulting in slower creep strain rate in the high-Nb alloy. In comparison, mainly superlattice intrinsic stacking faults enriched in Co, Cr, Nb and Mo were found in the low-Nb alloy. Following the results presented here, and those available in the literature, an atomic-scale driven alloy design approach that controls and promotes local phase transformation along planar faults at 750°C is proposed, aiming to design superalloys with enhanced creep resistance. Graphical abstract: Image, graphical abstract